Iron Sulfide Nanoparticles Embedded Into a Nitrogen and Sulfur Co-doped Carbon Sphere as a Highly Active Oxygen Reduction Electrocatalyst - Wang, Haitao; Qiu, Xiaoyu; Wang, Wei; Jiang, Lipei; Liu, Hongfang (Frontiers in Chemistry, 2019)
The unique micro/mesoporous spherical nanostructure composed of non-noble metal nanoparticles encapsulated within a heteroatom-doped carbon matrix provides great advantages for constructing advanced nonprecious oxygen reduction (ORR) electrocatalysts. Herein, a promising oxygen electrocatalyst comprising iron sulfide (Fe1-xS) nanoparticles embedded into nitrogen and sulfur co-doped carbon sphere (Fe1-xS/NS-CS) is successfully explored through a simple and fast polymerization between methylolmelamines (MMA) and ammonium ferric citrate (AFC), as well as high-temperature vulcanization process. Moreover, the proposed polymerization reaction can be finished completely within a very short time, which are useful for large-scale manufacturing. Impressively, the as-developed Fe1-xS/NS-MCS catalyst demonstrates an outstanding ORR catalytic activity in terms of more positive onset and half-wave potential, as well as much better methanol tolerance and stability, in comparison with that of Pt/C benchmarked catalyst. The remarkable ORR electrocatalytic properties are strong associated with the favorable characteristic spherical N, S co-doped porous graphitic carbon nanoskeleton incorporated with the Fe1-xS nanoparticle-encapsulation structure.